Appropriate Technology for Municipal Solid Waste Management Based on Wastepreneurship Implementation - Prihandoko, Diananto; Budiman, Arief; Setyono, Prabang; Fandelli, Chafid; Budiastuti, Maria Theresia Sri (ASEAN Journal of Chemical Engineering, 2021)
Piyungan landfill is the biggest landfill in the Special Region of Yogyakarta, Indonesia, which receives municipal solid waste (MSW) from two districts and a city, while its designed service time has been over and faces operational obstacles. Meanwhile, the volume of the MSW grows rapidly and exceeds the reduction rate in their sources. The difficulty in finding a new landfill area is the reason why appropriate technological alternatives in the MSW management are strongly needed. Therefore, the study aimed to evaluate the social and economic aspects and formulate appropriate technology based on the waste entrepreneurship (wastepreneurship) concept. The methods of this study were conducting calculation of waste characteristics and composition, social evaluation, and economic evaluation of the combination of composting, incinerator, and sanitary landfill. Waste characteristics and composition were taken using direct field measurement following Indonesia’s National Standard Guideline about retrieving and measuring examples of urban waste emergence and composition. Characteristics of waste are used for the calculation of calorific value and energy. The social evaluation was conducted using an in-depth interview with the rag pickers. The economic evaluation was conducted using net present value, internal rate of return, and payback period. The result of the study shows that Piyungan Landfill with total combustion waste reach 82.22% has the potential of incinerator implementation. In social evaluation, the implementation of composting and incinerator technologies would open employment for the surrounding community and rag pickers. The economic evaluation shows the combination of composting and incinerator technologies was economically feasible with an average profit margin of 12.97% in the operational period of 18 years. In conclusion, the concept of wastepreneurship is relevant in Piyungan Landfill by adjusting the MSW management paradigm from previously cost-center into business-center.